The reliability and validity of the pediatrics quality of life inventory (TM) (PedsQL) diabetes module 3.0 for Turkish adolescents with type 1 diabetes - ÇÖVENER ÖZÇELİK, ÇAĞRI (SPRINGER INDIA, 2015)
Adolescents might experience difficulties in compliance to diabetes management and their quality of life might be adversely affected. No specific quality of life scale is available in Turkey for adolescents aged 13-18 years with diabetes. The aim of the study was to examine the psychometric properties of the PedsQL (TM) 3.0 Diabetes Module (PedsQL (TM) 3.0 DM) Teen and Parent Reports (Ages 13-18) in Turkish adolescents with type 1 diabetes. One hundred and four adolescents aged 13-18 years with type 1 diabetes and their parents who presented at a diabetes center participated in this study. Content, construct, and concurrent validities, internal consistency reliability and item-total correlations were analyzed in order to determine the psychometric properties of the scales. Construct validity was evaluated with explanatory factor analysis. The factor structure of the Turkish version PedsQL (TM) diabetes module consisted of four subscales and did not support the original five-factor structure. Concurrent validity was analysed with Spearman Correlation and a positive significant correlation was found between PedsQL (TM) 3.0 DM and PedsQL (TM) 4.0 Generic Core Scales. Cronbach's alpha was found to be 0.92 for child self-reports (CSR) and 0.88 for parent proxy-report (PPR) of PedsQL (TM) 3.0DM. The psychometric analyses of the Turkish version of PedsQL (TM) 3.0 DM Teen and Parent Reports indicate high reliability and good content and construct validity for measuring diabetes-specific health related quality of life in Turkish adolescents with type 1 diabetes.
Keywords: Quality of life; Type 1 diabetes mellitus; Adolescent; Validity; Reliability; Turkey; GENERIC CORE SCALES; CHILDREN; VERSION